(untitled) (Quest Journal of Management and Social Sciences, 2024)
Purpose: The purpose of the study is to examine the influence of individual work-related factors (i.e., workload, work-life balance, job satisfaction, and social support) on productivity among young IT professionals working remotely through the mediating effect of work stress. Design/methodology/approach: This study employed a cross-sectional design and adopted a quantitative approach to analyse the data gathered from 271 respondents, selected through purposive sampling. Both direct and indirect structural relationship was analysed through Smart PLS 4.0. Findings: The results indicated that workload, work-life balance, and job satisfaction were significant predictors of employee performance, with work stress also having a mediating effect on these variables. The findings strongly support SET, EDT, JD-R, and work-family border theory. Conclusion: Productivity is sustained through task completion and balanced and satisfying work experiences that accommodate personal and professional needs. The study also exhibits the importance of mitigating stress management in contemporary work management and meeting the needs of the younger generation, which can lead to enhanced engagement. Practical Implications: In order to meet the needs of the younger generation, organisations must create flexible work policies that incorporate hybrid work models, support employees’ well-being by implementing stress management initiatives, and create comprehensive guidelines to handle issues like burnout, distractions, social connectivity, and team engagement in remote settings. Originality/Value: By integrating the perspectives from HRM and organisational psychology, this study provides a holistic model and addresses a critical gap in the literature, particularly in remote work practices, specifically for young employees in the IT sector. Keywords: Employee productivity, IT sector, remote work, young cohorts Paper Type: Research Paper JEL Classification: J24, J28, J86, M54